Photocatalytic Degradation of 2,4-Dichlorophenol by TiO2 Intercalated Talc Nanocomposite - Manqing Ai; Wenli Qin; Tian Xia; Ying Ye; Xuegang Chen; Pingping Zhang (International Journal of Photoenergy)
Novel nanocomposites have been prepared by intercalating TiO2 nanoparticles into talc. The nanocomposites have been verified by X-ray diffraction (XRD) from the appearance of a characteristic diffraction peak of TiO2. Thermal behavior of the prepared samples is examined by thermogravimetric analyzer (TGA), scanning electron microscope (SEM), and energy dispersive spectrometer (EDS), which have shown no TiO2 particles on the surface of the talc. The TiO2 particles are found in the layers of talc by transmission electron microscopy (TEM) and the Brunauer-Emmett-Teller (BET) method, which have shown the increase of specific surface areas and total pore volumes and the decline of average pore diameters. As the strong adsorption ability of talc can intensify the power of photon absorption and capture-recombination carriers, more than 99.5% of 2,4-dichlorophenol can be degraded in 1 h by the nanocomposite under an ultraviolet lamp in neutral solution and room temperature after reaching adsorption equilibrium, and the result of adsorbance is in accord with the first-order kinetic. The degradation rate was maintained at about 99% after 20 times. Therefore, the prepared talc/TiO2 nanocomposite is an efficient, stable, and recyclable material for wastewater treatment.